Adolescent body composition and associations with body size and growth from birth to late adolescence. The Tromsø study: Fit Futures—A Norwegian longitudinal cohort study. Issue 5 (27th December 2018) - Evensen, Elin; Emaus, Nina; Furberg, Anne‐Sofie; Kokkvoll, Ane; Wells, Jonathan; Wilsgaard, Tom; Winther, Anne; Skeie, Guri
Summary: Background: Fat and fat‐free masses and fat distribution are related to cardiometabolic risk. Objectives: to explore how birth weight, childhood body mass index (BMI) and BMI gain were related to adolescent body composition and central obesity. Methods: In a population‐based longitudinal study, body composition was measured by dual‐energy X‐ray absorptiometry in 907 Norwegian adolescents (48% girls). Associations between birth weight, BMI categories, and BMI gain were evaluated by fitting linear mixed models and conditional growth models with fat mass index (FMI, kg/m 2 ), fat‐free mass index (FFMI, kg/m 2 ) standard deviation scores (SDS), and central obesity at 15 to 20 years, as well as change in FMI SDS and FFMI SDS between ages 15 to 17 and 18 to 20 as outcomes. Results: Birth weight was associated with FFMI in adolescence. Greater BMI gain in childhood, conditioned on prior body size, was associated with higher FMI, FFMI, and central overweight/obesity with the strongest associations seen at age 6 to 16.5 years: FMI SDS: β = 0.67, 95% CI (0.63‐0.71), FFMI SDS: 0.46 (0.39, 0.52), in girls, FMI SDS: 0.80 (0.75, 0.86), FFMI SDS: 0.49 (0.43, 0.55), in boys. Conclusions: Compared with birth and early childhood, high BMI and greater BMI gain at later ages are strong predictors of higher fat mass and central overweight/obesity at 15 to 20 years of age.